Single pot bioconversion of prairie cordgrass into biohydrogen by thermophiles. (October 2018) - Bibra, Mohit; Kumar, Sudhir; Wang, Jia; Bhalla, Aditya; Salem, David R.; Sani, Rajesh K.
Graphical abstract: Highlights: First report of using prairie cord grass (PCG) to make biohydrogen (BioH2 ). Increased H2 production from 1.07 mmol H2 /g of PCG to 3.74 mmol H2 /g PCG. Omitted requirement of an inert gas for creating anaerobic conditions. Application of in-situ produced thermostable enzymes for biofuel production. Abstract: The aim of the present work was to use a thermophilic consortium for H2 production using lignocellulosic biomass in a single pot. The thermophilic consortium, growing at 60 °C utilized both glucose and xylose, making it an ideal source of microbes capable of utilizing and fermenting both hexose and pentose sugars. The optimization of pH, temperature, and substrate concentration increased the H2 production from 1.07 mmol H2 /g of prairie cordgrass (PCG) to 2.2 mmol H2 /g PCG by using the thermophilic consortium. A sequential cultivation of a thermostable lignocellulolytic enzyme producing strain Geobacillus sp. strain WSUCF1 (aerobic) with the thermophilic consortium (anaerobic) further increased H2 production with PCG 3-fold (3.74 mmol H2 /g PCG). A single pot sequential culturing of aerobic and anaerobic microbes can be sustainable and advantageous for industrial scale production of biofuels.